RELATIONSHIP IN MOTHER’S PERSONALITY WITH HEALTHY BEHAVIOR IN AUTISTIC CHILDREN WITH CARERING MEDIATION IN THE TIME OF THE COVID-19 PANDEMIC - Eny Dwi Harsiwi; Endang Widyorini; Maria Yang Roswita (Universitas Mercu Buana Jakarta, 2021)
Healthy behavior implementation is a main priority during this Covid-19 pandemic, especially for children with autistic disorder. Children with autistic disorder have a high risk of transmission if there is no help associated with health problems accompaniment. The purpose of this study is to determine whether there is an effect of personality traits (extraversion, agreeableness, conscientiousness, neuroticism, and openness) on health behavior for children with autism, mediated by parenting in the COVID-19 pandemic. The study participants included 31 mothers who have children with ASD aged 6-12 years with the Mild - Moderately category who live in the Central Java region and are cared for by their mothers. The research method used is a quantitative method using path analysis as a data analysis technique. The research measurement tools used a scale of health behavior, parenting scale, and Big Five Inventory (BFI) scale. The Results of the study found that there was an effect of personality traits (extraversion, agreeableness, conscientiousness and openness) on health behavior in children with autism, mediated by parenting in the COVID-19 pandemic.